Analysis of Semen Euphorbiae Frostlike Powders by HPLC Fingerprint - Wang, Yi-Shuo; Song, Gen-Wei; Zhang, Hong-Wei; Wu, Rui-Huan; Zhang, Zhen-Ling (Asian Journal of Chemistry, 2013)
In present work, the analysis method of semen euphorbiae frostlike powders with HPLC fingerprint was established. The high performance liquid chromatography was applied. The chromatographic column was Agilent Zorbax-C18 (4.6 × 250 mm, 5 μm) column. The flow phase was acetonitrile:water = 61:39; the flow velocity was: 1 mL min-1, the detection wavelength was 280 nm and the column temperature was 40 °C. The fingerprints of semen euphorbiae frostlike powders were established and 7 common peaks were identified. Fingerprint of semen euphorbiae frostlike powder samples and that of the control group shared a similarity of at least 0.9 and can be used in the qualitative identification of semen euphorbiae frostlike powders.